Synthesis of 6,19-sulfamidate bridged pregnanes - Duran, Fernando Javier (2005)
Conformationally restrained substituted pregnane-20-one derivatives were obtained by an intramolecular nitrene addition onto a C-5/C-6 double bond involving a tethered C-19 sulfamoyl moiety. The resulting aziridine underwent regioselective nucleophilic ring opening at C-5 at room temperature with cyanide, fluoride, and acetate. In the isolated case of acetate, a reversal of regioselectivity was observed at higher temperatures, a result attributed to a rearrangement process involving aziridine ring opening at the C-5 position and subsequent migration of the acetyl meiety to C-6.